Transarterial chemoembolization plus apatinib for unresectable hepatocellular carcinoma: a multicenter, randomized, open-label, phase III trial - Xue-Feng Kan; Bin Liang; Xiao-Lin Zhang; Lei Yu; Yao-Chang Luo; Shi Zhou; Rui-Bao Liu; Guo-Hui Xu; Hai-Liang Li; Zheng-Yin Liao; Hua Xiang; Wei Lu; et al. (BMC Medicine)
Abstract Background This study aimed to assess the efficacy and safety of transarterial chemoembolization (TACE) in combination with apatinib (TACE-apatinib) for patients with unresectable hepatocellular carcinoma (HCC). Methods This study was a multicenter, randomized, open-label, prospective, phase III trial. Patients with unresectable HCC were randomly assigned in a 1:1 ratio to receive either TACE-apatinib or TACE-alone treatment. Patients in the TACE-apatinib group began with a dosage of 500 mg/day of oral apatinib administered 4 days after the first TACE. The primary endpoint of this study was progression-free survival (PFS). The secondary endpoints included overall survival (OS), objective response rate (ORR), disease control rate (DCR), time to untreatable (unTACEable) progression (TTUP), and safety assessment. Results From November 1, 2018 to November 18, 2021, a total of 196 patients were randomly assigned to either the TACE-apatinib (n = 86) or TACE-alone (n = 92) group. The median PFS in the TACE-apatinib group was significantly longer than that of in the TACE-alone group (6.1 months vs. 3.4 months, p < 0.0001). The median OS was significantly prolonged in the TACE-apatinib group compared to the TACE-alone group (28.9 months vs. 24.0 months, p = 0.0005). The median TTUP in the TACE-apatinib group was 26.8 months, which was significantly longer than that of 20.1 months in the TACE-alone group (p = 0.0003). A significantly higher ORR and DCR were observed in the TACE-apatinib group compared to the TACE-alone group (ORR: 58.1% vs. 31.5%, p < 0.001; DCR: 87.2% vs. 69.6%, p = 0.004). Most of the treatment-related adverse events were grades 1–2, and no treatment-related deaths were observed. Conclusions Apatinib significantly improved the treatment effects of TACE for patients with unresectable HCC. TACE-apatinib could serve as a promising treatment option for this patient population, offering notable survival benefits while maintaining an acceptable safety profile. Trial registration Chinese Clinical Trial Register, No. ChiCTR1800018621.